Polishing composition
By introducing silica particles, alkaline compounds, and a specific ratio of water-soluble polymers into the grinding composition, the product of zeta potential and etching rate is controlled, solving the problems of defects and surface quality during the grinding process and achieving a highly efficient and high-quality grinding effect.
Patent Information
- Application Number
- CN202380043492.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2023-03-20
- Publication Date
- 2025-01-10
AI Technical Summary
Existing polishing compositions are ineffective at reducing defects such as LPD-N and micro-scratches when polishing semiconductor substrates, and the surface quality needs to be improved.
A grinding composition comprising silica particles, an alkaline compound, a first water-soluble polymer, a second water-soluble polymer, and water is used. By controlling the product of zeta potential and etching rate within a specific range, the dispersibility and substrate protection performance of the composition are optimized.
It achieves the reduction of defects and improvement of surface quality after grinding, especially LPD-N and micro-scratches, to obtain a high-quality ground surface.
Smart Images

Figure BDA0005158098710000131 
Figure BDA0005158098710000401
Abstract
Description
Technical Field
[0001] The present invention relates to a polishing composition. This application claims priority based on Japanese Patent Application No. 2022-58671 filed on March 31, 2022, the entire contents of which are incorporated herein by reference. Background Art
[0002] A polishing composition is used to precisely grind the surface of a material such as a metal or semi-metal, a non-metal, or an oxide thereof. For example, the surface of a silicon wafer used as a component of a semiconductor device is usually finished into a high-quality mirror surface through a grinding process (rough grinding process) and a polishing process (precision grinding process). The polishing process typically includes a pre-polishing process (pre-grinding process) and a fine polishing process (final grinding process). As technical documents related to the polishing composition mainly used in the use of grinding semiconductor substrates such as silicon wafers, patent documents 1 to 3 can be cited.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 6185432
[0006] Patent Document 2: Japanese Patent No. 6348927
[0007] Patent Document 3: Japanese Patent No. 6232243 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In the grinding composition, a composition with a grinding ability to grind the grinding object efficiently is used. For example, when grinding a substrate such as a semiconductor substrate such as the above-mentioned silicon wafer, the mechanical grinding effect produced by the abrasive particles and the chemical grinding effect (alkali etching) produced by the alkaline compound can be used to exert a higher processing force. The grinding composition with high processing force can improve manufacturing efficiency and cost-effectiveness, which is preferred. In this grinding, by using silicon dioxide particles as abrasive particles, a grinding surface with good quality can be efficiently achieved.
[0010] In addition, the polishing composition used for the polishing of the above-mentioned substrates, such as the polishing composition used for the fine polishing process (especially the fine polishing process of semiconductor substrates such as silicon wafers and other substrates), is required to achieve high-quality surface performance after polishing. The improvement of the surface quality of the polished surface can be achieved by making the polishing composition contain a water-soluble polymer, and using the above-mentioned water-soluble polymer to protect the substrate from alkaline etching. For example, patent documents 1 to 3 disclose a polishing composition comprising silica particles, an alkaline compound and a water-soluble polymer. However, in this polishing composition comprising abrasive particles, an alkaline compound and a water-soluble polymer, there is still room for improvement in reducing defects (such as LPD-N (Light Point Defect Non-cleanable), micro scratches (such as haze line), and improving the surface quality after polishing.
[0011] Therefore, an object of the present invention is to provide a polishing composition that can realize a high-quality surface.
[0012] Solutions for solving problems
[0013] According to the present specification, a polishing composition is provided. The polishing composition comprises: silica particles (A) as abrasive particles, a basic compound (B), a first water-soluble polymer (C1), a second water-soluble polymer (C2) and water (D). Here, the first water-soluble polymer (C1) is a polyvinyl alcohol-based polymer. The product (ER×ζ) of the etching rate ER [μm / h] of the polishing composition and the zeta potential ζ [mV] of the polishing composition is greater than or equal to -900nmV / h and less than or equal to -90nmV / h.
[0014] Here, the etching rate ER [μm / h] of the polishing composition is determined based on the following etching rate measurement.
[0015] [Etching rate measurement]
[0016] (1) The above-mentioned polishing composition is prepared as a chemical solution LE for etching rate measurement.
[0017] (2) Prepare a silicon single crystal substrate (rectangular shape with a length of 6 cm, a width of 3 cm, and a thickness of 775 μm) and measure its mass W0. The silicon single crystal substrate is immersed in a cleaning solution of NH4OH (29%):H2O2 (31%):deionized water (DIW) = 2:5.3:48 (volume ratio) at 25°C for 1 minute, and then immersed in a hydrogen fluoride (HF) aqueous solution (5%) at 25°C for 30 seconds.
[0018] (3) The silicon single crystal substrate was immersed in the chemical solution LE at 25° C. for 48 hours.
[0019] (4) The silicon single crystal substrate is taken out from the chemical solution LE and cleaned at 25°C for 10 seconds using a cleaning solution of NH4OH (29%): H2O2 (31%): deionized water (DIW) = 1:1:8 (volume ratio).
[0020] (5) The mass W1 of the cleaned silicon single crystal substrate is measured.
[0021] (6) The etching rate [μm / h] is calculated based on the difference between W0 and W1 and the specific gravity of the silicon single crystal substrate.
[0022] The Zeta potential ζ of the polishing composition can be an indicator of the dispersibility of the particles contained in the polishing composition. In addition, the etching rate ER of the polishing composition can be an indicator of the performance of protecting the surface of the polishing object from alkali etching of the polishing composition (hereinafter also referred to as "substrate protection performance"). The product (ζ×ER) of the Zeta potential ζ of the polishing composition disclosed herein and the etching rate ER is within the above range, so there is a tendency to control the dispersibility and substrate protection performance of the polishing composition in a well-balanced manner, and to achieve a high-quality surface with reduced defects (such as LPD-N) and micro scratches (such as haze lines) after polishing.
[0023] In some embodiments, the first water-soluble polymer (C1) is one or more selected from the group consisting of non-modified polyvinyl alcohol having a saponification degree of 70% or more, acetalized polyvinyl alcohol polymers, and polyvinyl alcohol polymers containing repeating units derived from alkyl vinyl ethers. When the above polymers are used as the first water-soluble polymer (C1), the surface quality after polishing tends to be further improved.
[0024] In some embodiments, the content of the first water-soluble polymer (C1) is 0.5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the abrasive. According to this composition, the effects of the technology disclosed herein can be preferably achieved.
[0025] In some embodiments, the second water-soluble polymer (C2) is one or more selected from the group consisting of a polyvinyl alcohol polymer having a chemical structure different from that of the first water-soluble polymer (C1), a polymer containing a nitrogen atom, and a polymer containing a (meth)acrylic acid unit. When the second water-soluble polymer (C2) is used together with the first water-soluble polymer (C1), the surface quality after polishing tends to be further improved.
[0026] In some embodiments, the nitrogen atom-containing polymer is a polymer containing a chain amide having an N-(meth)acryloyl group as a monomer unit. When this polymer is used together with the first water-soluble polymer (C1), the surface quality after polishing tends to be further improved.
[0027] In some embodiments, the content of the second water-soluble polymer (C2) is 0.5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the abrasive. According to this composition, the effects of the technology disclosed herein can be preferably achieved.
[0028] In some embodiments, the polishing composition further comprises a surfactant (E). According to this configuration, the surface quality after polishing tends to be further improved. In a preferred embodiment, the surfactant (E) is an anionic surfactant.
[0029] The polishing composition disclosed herein can be preferably used for polishing a surface formed of a silicon material. By polishing a surface formed of a silicon material using the polishing composition, a high-quality surface formed of a silicon material can be efficiently achieved.
[0030] The polishing composition disclosed herein may be a concentrated liquid. The polishing composition disclosed herein may be produced, distributed, and stored in the form of a concentrated liquid. DETAILED DESCRIPTION
[0031] The following describes a suitable embodiment of the present invention. It should be noted that matters necessary for the implementation of the present invention other than matters specifically mentioned in this specification can be grasped as conventional means by those skilled in the art based on the prior art in this field. The present invention can be implemented according to the contents disclosed in this specification and the technical common sense in this field.
[0032] <Characteristics of Polishing Composition>
[0033] The grinding composition disclosed herein is characterized by Zeta potential and etching rate. Here, the Zeta potential of the grinding composition refers to the Zeta potential measured for the grinding composition using a Zeta potential measuring device. More specifically, it refers to the Zeta potential measured for the particles contained in the grinding composition. The Zeta potential of the grinding composition can be an indicator of the dispersibility of the particles contained in the grinding composition. For example, the absolute value of the Zeta potential of the grinding composition with a negative Zeta potential becomes larger, indicating that in the grinding composition, the electrostatic repulsion of the particles containing abrasive particles increases, and there is a tendency to show that the dispersibility of the grinding composition is improved.
[0034] In addition, the etching rate of the grinding composition represents the degree of chemical corrosion (etching) of the surface of the grinding object by the alkaline compounds contained in the grinding composition. Specifically, the etching rate of the grinding composition is obtained based on the following etching rate measurement. Here, the water-soluble polymers contained in the grinding composition have a tendency to be adsorbed on the surface of the grinding object so as to protect the surface of the grinding object from etching. Therefore, the etching rate of the grinding composition can be an index of the following performance: under the condition of removing the influence of the mechanical action based on the abrasive, the performance of the phenomenon that the surface of the grinding object is etched by the alkaline compounds, etc., is the performance of the grinding composition protecting the surface of the grinding object (hereinafter, also referred to as substrate protection performance). In the embodiments described later, the etching rate of the grinding composition also adopts the value obtained based on the following etching rate measurement.
[0035] [Etching rate measurement]
[0036] (1) A polishing composition is prepared as a chemical solution LE for etching rate measurement.
[0037] (2) Prepare a silicon single crystal substrate (rectangular shape with a length of 6 cm, a width of 3 cm, and a thickness of 775 μm) and measure its mass W0. The silicon single crystal substrate is immersed in a cleaning solution of NH4OH (29%):H2O2 (31%):deionized water (DIW) = 2:5.3:48 (volume ratio) at 25°C for 1 minute, and then immersed in a hydrogen fluoride (HF) aqueous solution (5%) at 25°C for 30 seconds.
[0038] (3) The silicon single crystal substrate was immersed in the chemical solution LE at 25° C. for 48 hours.
[0039] (4) The silicon single crystal substrate is taken out from the chemical solution LE and cleaned at 25°C for 10 seconds using a cleaning solution of NH4OH (29%): H2O2 (31%): deionized water (DIW) = 1:1:8 (volume ratio).
[0040] (5) The mass W1 of the cleaned silicon single crystal substrate is measured.
[0041] (6) The etching rate [μm / h] is calculated based on the difference between W0 and W1 and the specific gravity of the silicon single crystal substrate.
[0042] The product of the zeta potential and the etching rate of the polishing composition disclosed herein is within a specified range. The product of the zeta potential and the etching rate of the polishing composition being within a specified range indicates that the dispersibility of the polishing composition and the substrate protection performance of the polishing composition tend to be controlled and within the specified range respectively. According to the polishing composition of this configuration, the surface quality after polishing tends to be improved.
[0043] According to one embodiment of the technology disclosed herein, the product (ER×ζ) of the Zeta potential ζ [mV] of the polishing composition and the etching rate ER [μm / h] of the polishing composition is greater than -900nmV / h and less than -90nmV / h. When the product of the Zeta potential and the etching rate is within the above range, the dispersibility and substrate protection performance of the polishing composition are well balanced, and there is a tendency to achieve a high-quality surface with reduced defects (e.g., LPD-N) and micro scratches (e.g., haze lines) after polishing.
[0044] From the perspective of improving surface quality such as reducing LPD-N and reducing haze lines after grinding, the product (ER×ζ) of the Zeta potential ζ[mV] of the grinding composition and the etching rate ER[μm / h] of the grinding composition is more preferably -870nmV / h or more. In some embodiments, the above-mentioned ER×ζ can be -700nmV / h or more, -500nmV / h or more, -400nmV / h or more, or -350nmV / h or more. Similarly, from the perspective of improving surface quality, the above-mentioned ER×ζ can be -100nmV / h or less, -105nmV / h or less, and more preferably -115nmV / h or less. In some embodiments, the above-mentioned ER×ζ can be -200nmV / h or less, -250nmV / h or less, -300nmV / h or less, or -400nmV / h or less.
[0045] The Zeta potential ζ of the grinding composition is not particularly limited as long as the product with the etching rate ER is a specific range. The above-mentioned Zeta potential ζ is usually less than 0mV, and from the viewpoints of the dispersibility of the grinding composition, the surface quality of the grinding surface, it is appropriate to be below -5mV, preferably below -10mV, more preferably below -20mV, further preferably below -25mV, and particularly preferably below -30mV. In some ways, the above-mentioned Zeta potential ζ can be below -35mV, below -38mV, or below -45mV. From the viewpoint of improving the grinding rate, it is preferably above -80mV, more preferably above -70mV, further preferably above -60mV, or above -45mV. The Zeta potential ζ of the grinding composition can be set by the type of abrasive, content, type of water-soluble polymer, molecular weight, content, type of alkaline compound, content, the presence or absence of the addition of other additives (surfactants, etc.), its type, content, pH, etc.
[0046] The zeta potential of the polishing composition can be measured using a known and commonly used zeta potential measuring device. Specifically, it can be measured using the method described in the examples described below.
[0047] The etching rate ER of the grinding composition is not particularly limited as long as the product with the Zeta potential ζ is in a specific range. From the viewpoint of the surface quality of the grinding surface, the etching rate ER of the grinding composition determined based on the above-mentioned etching rate is usually appropriate to be less than 25 μm / h, preferably less than 20 μm / h, and more preferably less than 18 μm / h. In some ways, the above-mentioned etching rate ER can be less than 13 μm / h, less than 10 μm / h, less than 8.5 μm / h, or less than 5 μm / h. From the viewpoint of the grinding rate, the above-mentioned etching rate ER is usually appropriate to be more than 2 μm / h, preferably more than 3 μm / h, more preferably more than 4 μm / h. In some ways, the above-mentioned etching rate ER can be more than 7 μm / h, more than 8 μm / h, more than 9 μm / h, or more than 10 μm / h. The etching rate ER of the polishing composition can be set by the type, molecular weight, and content of the water-soluble polymer, the type and content of the basic compound, the presence or absence of other additives (surfactants, etc.), their types, contents, pH, etc.
[0048] <Abrasive Grains>
[0049] The grinding composition disclosed herein contains silica particles as abrasive particles. The silica particles as abrasive particles play a role in mechanically grinding the surface of the grinding object. By making the grinding composition contain abrasive particles, the grinding rate can be increased based on the mechanical grinding effect caused by the abrasive particles. In addition, in a grinding composition that can be used for grinding (e.g., fine polishing) of a grinding object having a surface formed of silicon, such as a silicon wafer described later, it is particularly meaningful to use silica particles as abrasive particles.
[0050] As specific examples of silica particles, colloidal silica, fumed silica, precipitated silica, etc. can be cited. Silica particles can be used alone or in combination of two or more. From the aspect of easily obtaining a grinding surface with excellent surface quality after grinding, colloidal silica is particularly preferably used. As colloidal silica, for example, colloidal silica made by using water glass (sodium silicate) as a raw material by an ion exchange method and alkoxide method colloidal silica (colloidal silica manufactured by a hydrolysis condensation reaction of alkoxysilane) can be preferably used. Colloidal silica can be used alone or in combination of two or more.
[0051] The true specific gravity of the silicon dioxide constituting the silicon dioxide particles is preferably 1.5 or more, more preferably 1.6 or more, and further preferably 1.7 or more. The upper limit of the true specific gravity of silicon dioxide is not particularly limited, and is typically 2.3 or less, for example, 2.2 or less. The true specific gravity of the silicon dioxide particles can be a measured value obtained by a liquid substitution method using ethanol as a substitution liquid.
[0052] The average primary particle size of the abrasive (typically silica particles) is not particularly limited, and from the viewpoint of the grinding rate, it is preferably 5 nm or more, more preferably 10 nm or more. From the viewpoint of obtaining a higher grinding effect (such as a reduction in haze, removal of defects, etc.), the above-mentioned average primary particle size is preferably 15 nm or more, more preferably 20 nm or more (for example, more than 20 nm). In addition, from the viewpoint of preventing scratches, the average primary particle size of the abrasive is preferably 100 nm or less, more preferably 50 nm or less, and further preferably 45 nm or less. From the viewpoint of easily obtaining a surface with lower haze, in some embodiments, the average primary particle size of the abrasive can be 43 nm or less, less than 40 nm, less than 38 nm, less than 35 nm, less than 32 nm, or less than 30 nm.
[0053] It should be noted that in this specification, the average primary particle size refers to the specific surface area (BET value) measured by the BET method, and is calculated according to the formula: Average primary particle size (nm) = 6000 / (true density (g / cm 3 )×BET value (m 2 The above-mentioned specific surface area can be measured using, for example, a surface area measuring device manufactured by Micromeritics, trade name "Flow Sorb II 2300".
[0054] The average secondary particle size of the abrasive (typically silica particles) is not particularly limited, and can be appropriately selected from a range of about 15 nm to 300 nm, for example. From the viewpoint of increasing the grinding rate, the above-mentioned average secondary particle size is preferably greater than 30 nm, and more preferably greater than 35 nm. In some embodiments, the above-mentioned average secondary particle size can be, for example, greater than 40 nm, or greater than 42 nm, and preferably greater than 44 nm. In addition, it is generally advantageous for the above-mentioned average secondary particle size to be less than 250 nm, preferably less than 200 nm, and more preferably less than 150 nm. In some preferred embodiments, the above-mentioned average secondary particle size is less than 120 nm, more preferably less than 100 nm, and further preferably less than 70 nm, for example, less than 60 nm, and also less than 50 nm.
[0055] In this specification, the average secondary particle size refers to the particle size (volume average particle size) measured by the dynamic light scattering method. The average secondary particle size of the abrasive can be measured by the dynamic light scattering method using, for example, Nanotrac UPA-UT151 manufactured by Nikkiso Co., Ltd.
[0056] The shape (outer shape) of the silica particles may be spherical or non-spherical. Specific examples of non-spherical particles include peanut-shaped (i.e., the shape of peanut shells), cocoon-shaped, candy-shaped, rugby-shaped, etc. For example, silica particles having mostly peanut-shaped or cocoon-shaped particles may be preferably used.
[0057] Although not particularly limited, the average value (average aspect ratio) of the major diameter / minor diameter ratio of the silica particles is in principle more than 1.0, preferably more than 1.05, more preferably more than 1.1, and may be more than 1.2. With the increase of the average aspect ratio, a higher polishing rate can be achieved. In addition, from the viewpoint of reducing scratches, the average aspect ratio of the silica particles is preferably less than 3.0, more preferably less than 2.0, more preferably less than 1.5, and may be less than 1.4.
[0058] The shape (outer shape) and average aspect ratio of silica particles can be grasped, for example, by electron microscope observation. As a specific step to grasp the average aspect ratio, for example, a scanning electron microscope (SEM) is used to draw the smallest rectangle circumscribed to each particle image for a specified number (e.g., 200) of silica particles with identifiable independent particle shapes. Then, for each rectangle drawn for each particle image, the length of its long side (the value of the long diameter) is calculated and divided by the length of the short side (the value of the short diameter) to obtain the value as the long diameter / short diameter ratio (aspect ratio). The aspect ratios of the above-mentioned specified number of particles are arithmetic averaged, thereby obtaining the average aspect ratio.
[0059] The polishing composition disclosed herein may also contain abrasives other than silica particles (hereinafter also referred to as "non-silica abrasives") within a range that does not significantly hinder the effect of the present invention. Examples of non-silica abrasives include inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include: oxide particles such as aluminum oxide particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and iron red particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; carbonates such as calcium carbonate and barium carbonate, etc. Specific examples of organic particles include polymethyl methacrylate (PMMA) particles, poly(meth)acrylic acid particles (here (meth)acrylic acid means including acrylic acid and methacrylic acid), polyacrylonitrile particles, etc. Such abrasives can be used alone or in combination of two or more.
[0060] The technology disclosed herein can be preferably implemented in a manner that substantially only silica particles are used as abrasive particles. From such a viewpoint, it is appropriate that the proportion of silica particles in the total amount of abrasive particles is 90% by weight or more, preferably 95% by weight or more, and more preferably 98% by weight or more (e.g., 99 to 100% by weight).
[0061] <Basic Compounds>
[0062] The grinding composition disclosed herein contains a basic compound. In this specification, a basic compound refers to a compound having a function of being dissolved in water and raising the pH of an aqueous solution. By making the grinding composition contain a basic compound, the grinding object can be efficiently ground by its chemical grinding action (alkali etching). As the basic compound, an organic or inorganic basic compound containing nitrogen, a basic compound containing phosphorus, a hydroxide of an alkali metal, a hydroxide of an alkaline earth metal, various carbonates, bicarbonates, etc. can be used. As examples of basic compounds containing nitrogen, quaternary ammonium compounds, ammonia, amines (preferably water-soluble amines) and the like can be cited. As examples of basic compounds containing phosphorus, quaternary phosphonium compounds can be cited. Such basic compounds can be used alone or in combination of two or more.
[0063] As specific examples of alkali metal hydroxides, potassium hydroxide, sodium hydroxide, etc. can be listed. As specific examples of carbonates or bicarbonates, ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, etc. can be listed. As specific examples of amines, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, anhydrous piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, guanidine, imidazole, triazole and other azoles can be listed. As specific examples of quaternary phosphonium compounds, quaternary phosphonium hydroxides such as tetramethylphosphonium hydroxide and tetraethylphosphonium hydroxide can be listed.
[0064] As the quaternary ammonium compound, a quaternary ammonium salt (typically a strong base) such as a tetraalkylammonium salt or a hydroxyalkyltrialkylammonium salt can be used. The anion component in the quaternary ammonium salt can be, for example, OH - 、F - , Cl - Br - ,I - 、ClO4 - 、BH4 - As examples of the above-mentioned quaternary ammonium compounds, there can be cited quaternary ammonium salts whose anions are OH-, i.e., quaternary ammonium hydroxides. As specific examples of quaternary ammonium hydroxides, there can be cited tetraalkylammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide, and tetrahexylammonium hydroxide; hydroxyalkyltrialkylammonium hydroxides such as 2-hydroxyethyltrimethylammonium hydroxide (also called choline), and the like.
[0065] Among these basic compounds, for example, at least one basic compound selected from the group consisting of alkali metal hydroxides, quaternary ammonium hydroxides and ammonia can be preferably used. Among them, tetraalkylammonium hydroxides (such as tetramethylammonium hydroxide) and ammonia are more preferred, and ammonia is particularly preferred.
[0066] <Water-soluble polymer>
[0067] The polishing composition disclosed herein comprises a water-soluble polymer. The water-soluble polymer can help protect the surface of the polishing object, improve the wettability of the polishing object surface after polishing, etc. The polishing composition disclosed herein is characterized in that it comprises at least two water-soluble polymers. In other words, the polishing composition disclosed herein comprises a first water-soluble polymer and a second water-soluble polymer.
[0068] <First water-soluble polymer>
[0069] The grinding composition disclosed herein comprises a polyvinyl alcohol polymer as the first water-soluble polymer. According to the grinding composition comprising the polyvinyl alcohol polymer, a high-quality grinding surface is easily obtained. Although not particularly restrictive, it is believed that the polyvinyl alcohol polymer protects the substrate surface by acting on the substrate surface, thereby contributing to improving the grinding surface quality (specifically, reducing the haze). By using the polyvinyl alcohol polymer as the first water-soluble polymer in combination with the second water-soluble polymer, it is possible to enjoy the advantages based on the different effects of each water-soluble polymer, and effectively achieve high surface quality.
[0070] In this specification, a polyvinyl alcohol polymer refers to a polymer containing a vinyl alcohol unit (hereinafter also referred to as a "VA unit") as its repeating unit. One type of the polyvinyl alcohol polymer may be used alone, or two or more types may be used in combination. The polyvinyl alcohol polymer may contain only VA units as repeating units, or may contain repeating units other than VA units (hereinafter also referred to as "non-VA units") in addition to VA units. The polyvinyl alcohol polymer may be a random copolymer containing VA units and non-VA units, a block copolymer, an alternating copolymer, or a graft copolymer. The polyvinyl alcohol polymer may contain only one type of non-VA unit, or may contain two or more types of non-VA units.
[0071] The above-mentioned polyvinyl alcohol-based polymer may be unmodified polyvinyl alcohol (unmodified PVA) or modified polyvinyl alcohol (modified PVA). Here, unmodified PVA refers to a polyvinyl alcohol-based polymer produced by hydrolyzing (saponifying) polyvinyl acetate, which does not substantially contain repeating units other than repeating units (-CH2-CH(OCOCH3)-) and VA units of a structure formed by vinyl polymerization of vinyl acetate. The saponification degree of the above-mentioned unmodified PVA may be, for example, 60% or more, and from the viewpoint of water solubility, may be 70% or more, 80% or more, or 90% or more. In some embodiments, the saponification degree of unmodified PVA may be 98% or more (completely saponified).
[0072] The polyvinyl alcohol polymer can be a modified PVA comprising a VA unit and a non-VA unit, wherein the non-VA unit has at least one structure selected from an oxyalkylene group, a carboxyl group, a (di) carboxyl group, a (di) carboxylate group, a phenyl group, a naphthyl group, a sulfonic acid group, an amino group, a hydroxyl group, an amide group, an imide group, a nitrile group, an ether group, an ester group and their salts. In addition, as a non-VA unit that can be included in the modified PVA, for example, it can be a repeating unit derived from an N-vinyl monomer, an N-(methyl)acryloyl monomer, a repeating unit derived from ethylene, a repeating unit derived from an alkyl vinyl ether, a repeating unit derived from a vinyl ester of a monocarboxylic acid having more than 3 carbon atoms, a repeating unit derived from a (di)acetone compound, etc., but is not limited to these. As a suitable example of the above-mentioned N-vinyl monomer, N-vinyl pyrrolidone can be cited. As a suitable example of the above-mentioned N-(methyl)acryloyl monomer, N-(methyl)acryloyl morpholine can be cited. The alkyl vinyl ether may be, for example, a vinyl ether having an alkyl group having 1 to 10 carbon atoms, such as propyl vinyl ether, butyl vinyl ether, and 2-ethylhexyl vinyl ether. The vinyl ester of a monocarboxylic acid having 3 to 3 carbon atoms may be, for example, a vinyl ester of a monocarboxylic acid having 3 to 7 carbon atoms, such as vinyl propionate, vinyl butyrate, vinyl valerate, and vinyl hexanoate. Preferred examples of the (di)acetone compound include diacetone (meth)acrylamide and acetylacetone.
[0073] In addition, in some preferred embodiments, an acetalized polyvinyl alcohol polymer can be used as the polyvinyl alcohol polymer. As the acetalized polyvinyl alcohol polymer, for example, a modified PVA in which a part of the VA units contained in the polyvinyl alcohol polymer is acetalized can be cited. The modified PVA in which a part of the VA units contained in the above-mentioned polyvinyl alcohol polymer is acetalized (acetalized PVA (ac-PVA)) can be obtained by reacting a part of the hydroxyl groups of the polyvinyl alcohol polymer with an aldehyde compound or a ketone compound for acetalization. Typically, the acetalized polyvinyl alcohol polymer can be obtained by an acetalization reaction of a polyvinyl alcohol polymer with an aldehyde compound. In some preferred embodiments, the carbon number of the above-mentioned aldehyde compound is 1 to 7, and more preferably 2 to 7.
[0074] Examples of the aldehyde compound include: formaldehyde; linear or branched alkyl aldehydes such as acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, tert-butyraldehyde, and hexanal; alicyclic or aromatic aldehydes such as cyclohexanecarboxaldehyde and benzaldehyde. These may be used alone or in combination of two or more. In addition to formaldehyde, an aldehyde compound in which one or more hydrogen atoms are substituted by a halogen or the like may be used. Among these, linear or branched alkyl aldehydes are preferred from the viewpoint of high solubility in water and easy acetalization reaction, and acetaldehyde, n-propionaldehyde, n-butyraldehyde, and n-valeraldehyde are more preferred.
[0075] As the aldehyde compound, in addition to the above, aldehyde compounds having 8 or more carbon atoms, such as 2-ethylhexanal, nonanal, and decanal, can be used.
[0076] The acetalized polyvinyl alcohol polymer includes a VA unit which is a structural part represented by the following chemical formula: -CH2-CH(OH)-, and an acetalized structural unit represented by the following general formula (1) (hereinafter also referred to as a "VAC unit").
[0077]
[0078] (In formula (1), R is a hydrogen atom, or a straight-chain or branched alkyl group, which may be substituted by a functional group.)
[0079] In some preferred embodiments, R in the above formula (1) is a hydrogen atom, or a linear or branched alkyl group having 1 to 6 carbon atoms. R may be one of them, or a combination of two or more thereof. From the viewpoint of improving haze reduction performance, R is preferably a linear or branched alkyl group having 1 to 6 carbon atoms.
[0080] From the viewpoint of improving haze reduction performance, the acetalization degree of the acetalized polyvinyl alcohol polymer can be set to 1 mol% or more, can be 5 mol% or more, preferably 10 mol% or more, more preferably 15 mol% or more, further preferably 20 mol% or more, particularly preferably 25 mol% or more (e.g. 27 mol% or more). From the viewpoint of improving hydrophilicity, the acetalization degree of the acetalized polyvinyl alcohol polymer is preferably set to less than 60 mol%, further 50 mol% or less, more preferably 40 mol% or less, particularly preferably 35 mol% or less (e.g. 33 mol% or less). It should be noted that, in this specification, "acetalization degree" refers to the proportion of acetalized structural units (VAC units) in all repeating units constituting the acetalized polyvinyl alcohol polymer.
[0081] In addition, as the polyvinyl alcohol polymer, a cation-modified polyvinyl alcohol into which a cationic group such as a quaternary ammonium structure is introduced can also be used. As the above-mentioned cation-modified polyvinyl alcohol, for example, polyvinyl alcohol into which a cationic group derived from a monomer having a cationic group such as a diallyldialkylammonium salt, an N-(meth)acryloylaminoalkyl-N,N,N-trialkylammonium salt can be introduced can be cited. In addition, as the vinyl alcohol polymer, a non-VA unit having a chemical formula of: -CH2-CH(CR 1 (OR 4 )-CR 2 (OR 5 )-R 3 )-a polymer of the structural part shown. Here R 1 ~R 3Each independently represents a hydrogen atom or an organic group, R 4 and R 5 Each independently represents a hydrogen atom or R 6 -CO-(where R 6 For example, in the above chemical formula, R 1 ~R 3 When at least one of is an organic group, the organic group may be a linear or branched alkyl group having 1 to 8 carbon atoms. 6 The carbon number may be a linear or branched alkyl group having 1 to 8 carbon atoms.
[0082] In some embodiments, as the modified PVA, a modified PVA having a 1,2-diol structure in the side chain may be used. For example, as the modified PVA, a modified PVA containing the R 1 ~R 5 A modified PVA (butene glycol-vinyl alcohol copolymer (BVOH)) containing non-VA units containing hydrogen atoms.
[0083] The proportion of the molar number of VA units in the molar number of all repeating units constituting the polyvinyl alcohol polymer can be, for example, 5% or more, 10% or more, 20% or more, or 30% or more. Although not particularly limited, in some embodiments, the proportion of the molar number of the above-mentioned VA units can be 50% or more, 65% or more, 75% or more, 80% or more, or 90% or more (for example, 95% or more or 98% or more). The repeating units constituting the polyvinyl alcohol polymer can be substantially 100% VA units. Here, "substantially 100%" means that at least the polyvinyl alcohol polymer is not intentionally made to contain non-VA units. Typically, the proportion of the molar number of non-VA units in the molar number of all repeating units is less than 2% (for example, less than 1%), including the case of 0%. In some other embodiments, the proportion of the molar number of VA units in the molar number of all repeating units constituting the polyvinyl alcohol polymer can be, for example, less than 95%, less than 90%, less than 80%, or less than 70%.
[0084] The content of VA units in the polyvinyl alcohol polymer (content on a weight basis) can be, for example, 5% by weight or more, 10% by weight or more, 20% by weight or more, or 30% by weight or more. Although not particularly limited, in some embodiments, the content of the above-mentioned VA unit can be 50% by weight or more (for example, more than 50% by weight), 70% by weight or more, or 80% by weight or more (for example, 90% by weight or more, or 95% by weight or more, or 98% by weight or more). The repeating units constituting the polyvinyl alcohol polymer can be substantially 100% by weight VA units. Here, "substantially 100% by weight" means that at least non-VA units are not intentionally contained as repeating units constituting the polyvinyl alcohol polymer, and typically, the content of non-VA units in the polyvinyl alcohol polymer is less than 2% by weight (for example, less than 1% by weight). In some other embodiments, the content of VA units in the polyvinyl alcohol polymer can be, for example, less than 95% by weight, less than 90% by weight, less than 80% by weight, or less than 70% by weight.
[0085] The polyvinyl alcohol polymer may include multiple polymer chains with different contents of VA units in the same molecule. Here, the polymer chain refers to a part (chain segment) that constitutes a part of a molecule of the polymer. For example, the polyvinyl alcohol polymer may include a polymer chain A with a VA unit content higher than 50% by weight and a polymer chain B with a VA unit content lower than 50% by weight (i.e., a non-VA unit content higher than 50% by weight) in the same molecule.
[0086] The polymer chain A may contain only VA units as repeating units, or may contain non-VA units in addition to VA units. The content of VA units in the polymer chain A may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In some embodiments, the content of VA units in the polymer chain A may be 95% by weight or more, or 98% by weight or more. The repeating units constituting the polymer chain A may be substantially 100% by weight of VA units.
[0087] The polymer chain B may contain only non-VA units as repeating units, or may contain VA units in addition to non-VA units. The content of non-VA units in the polymer chain B may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In some embodiments, the content of non-VA units in the polymer chain B may be 95% by weight or more, or 98% by weight or more. The repeating units constituting the polymer chain B may be substantially 100% by weight of non-VA units.
[0088] As examples of polyvinyl alcohol-based polymers containing polymer chain A and polymer chain B in the same molecule, block copolymers and graft copolymers containing these polymer chains can be listed. The above-mentioned graft copolymer can be a graft copolymer having a structure in which polymer chain B (side chain) is grafted onto polymer chain A (main chain), or a graft copolymer having a structure in which polymer chain A (side chain) is grafted onto polymer chain B (main chain). In some embodiments, a polyvinyl alcohol-based polymer having a structure in which polymer chain B is grafted onto polymer chain A can be used.
[0089] Examples of polymer chain B include polymer chains having repeating units derived from N-vinyl monomers as main repeating units; polymer chains having repeating units derived from N-(meth)acryloyl monomers as main repeating units; polymer chains having repeating units derived from vinyl esters of dicarboxylic acids such as fumaric acid, maleic acid, and maleic anhydride as main repeating units; polymer chains having repeating units derived from aromatic vinyl monomers such as styrene and vinylnaphthalene as main repeating units; polymer chains having oxyalkylene units as main repeating units, etc. It should be noted that in this specification, unless otherwise specified, the main repeating unit refers to a repeating unit having a content exceeding 50% by weight.
[0090] As a suitable example of polymer chain B, there can be cited a polymer chain having N-vinyl monomers as main repeating units, i.e., N-vinyl polymer chains. The content of repeating units derived from N-vinyl monomers in the N-vinyl polymer chain typically exceeds 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. The polymer chain B may be substantially entirely composed of repeating units derived from N-vinyl monomers.
[0091] In this specification, examples of N-vinyl monomers include monomers having nitrogen-containing heterocycles (e.g., lactam rings), and N-vinyl chain amides. As specific examples of N-vinyl lactam monomers, N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl morpholinone, N-vinyl caprolactam, N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, etc. can be cited. As specific examples of N-vinyl chain amides, N-vinyl acetamide, N-vinyl propionamide, N-vinyl butyric acid amide, etc. can be cited. Polymer chain B, for example, can be an N-vinyl polymer chain in which more than 50% by weight (e.g., more than 70% by weight, or more than 85% by weight, or more than 95% by weight) of its repeating units are N-vinyl pyrrolidone units. The repeating units constituting polymer chain B can be substantially all N-vinyl pyrrolidone units.
[0092] As another example of polymer chain B, there can be cited a polymer chain having a repeating unit derived from an N-(meth)acryloyl type monomer as a main repeating unit, that is, an N-(meth)acryloyl polymer chain. The content of the repeating unit derived from the N-(meth)acryloyl type monomer in the N-(meth)acryloyl polymer chain typically exceeds 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. The polymer chain B may be substantially entirely composed of repeating units derived from N-(meth)acryloyl type monomers.
[0093] In the present specification, examples of N-(meth)acryloyl-type monomers include chain amides having N-(meth)acryloyl groups and cyclic amides having N-(meth)acryloyl groups. Examples of chain amides having N-(meth)acryloyl groups include (meth)acrylamide; N-alkyl(meth)acrylamide such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N-n-butyl(meth)acrylamide; and N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. Examples of the cyclic amide having an N-(meth)acryloyl group include N-(meth)acryloylmorpholine and N-(meth)acryloylpyrrolidine.
[0094] As another example of polymer chain B, there can be mentioned a polymer chain containing an oxyalkylene unit as a main repeating unit, that is, an oxyalkylene polymer chain. The content of the oxyalkylene unit in the oxyalkylene polymer chain is typically more than 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. The repeating units contained in polymer chain B may be substantially all oxyalkylene units.
[0095] Examples of oxyalkylene units include oxyethylene units, oxypropylene units, oxybutylene units, etc. Such oxyalkylene units may be repeating units derived from corresponding alkylene oxides, respectively. The oxyalkylene units contained in the oxyalkylene polymer chain may be one or more than two. For example, it may be an oxyalkylene polymer chain comprising a combination of oxyethylene units and oxypropylene units. In the oxyalkylene polymer chain comprising more than two oxyalkylene units, these oxyalkylene units may be random copolymers of corresponding alkylene oxides, may be block copolymers, may be alternating copolymers, or graft copolymers.
[0096] As other examples of the polymer chain B, there can be listed a polymer chain comprising repeating units derived from an alkyl vinyl ether (e.g., a vinyl ether having an alkyl group having 1 to 10 carbon atoms), a polymer chain comprising repeating units derived from a monocarboxylic acid vinyl ester (e.g., a vinyl ester of a monocarboxylic acid having 3 or more carbon atoms), a polymer chain into which a cationic group (e.g., a cationic group having a quaternary ammonium structure) is introduced, and the like.
[0097] In some embodiments of the technology disclosed herein, the polyvinyl alcohol-based polymer as the first water-soluble polymer is preferably a copolymer containing VA units and non-VA units, i.e., modified polyvinyl alcohol. In addition, the saponification degree of the modified polyvinyl alcohol-based polymer as the first water-soluble polymer is usually 50 mol% or more, preferably 65 mol% or more, more preferably 70 mol% or more, for example 75 mol% or more.
[0098] The weight average molecular weight (Mw) of the first water-soluble polymer (specifically, the polyvinyl alcohol polymer) can be set to, for example, 100×10 4 Below, 60×10 4 The following are appropriate. From the viewpoint of concentration efficiency, etc., the above Mw can be 30×10 4 Below, preferably 20×10 4 Below, for example, it can be 10×10 4 Below, can be 8×10 4 Below, can be 5×10 4 Below, it can also be 3×10 4 As the Mw of the polyvinyl alcohol polymer decreases, the dispersion stability of the polyvinyl alcohol polymer tends to improve. In addition, from the viewpoint of appropriately protecting the polished surface and maintaining or improving the surface quality, the Mw may be, for example, 0.2×10 4 Above, usually preferably 0.5×10 4 As the Mw of the polyvinyl alcohol polymer increases, the effect of protecting the polishing object and improving wettability tends to increase. From this point of view, in some embodiments, the Mw is 0.8×10 4 The above is appropriate, preferably 1.0×10 4 Above, it can be 2×10 4 Above, can be 3×10 4 Above, for example, it can be 4×10 4 Above, it can also be 5×10 4 above.
[0099] As the Mw of the water-soluble polymer, the molecular weight calculated by the value (water system, polyethylene oxide conversion) based on the aqueous gel permeation chromatography (GPC) can be used. The same is true for the Mw of the first water-soluble polymer and the second water-soluble polymer described later. As a GPC measuring device, the model name "HLC-8320GPC" made by Tosoh Corporation can be used. The measurement can be carried out, for example, according to the following conditions. The same method is also used for the embodiments described later.
[0100] [GPC measurement conditions]
[0101] Sample concentration: 0.1 wt%
[0102] Column: TSKgel GMPW XL
[0103] Detector: Differential Refractometer
[0104] Eluent: 100 mM sodium nitrate aqueous solution
[0105] Flow rate: 1mL / min
[0106] Measuring temperature: 40℃
[0107] Sample injection volume: 200 μL
[0108] Although not particularly limited, in some embodiments, the content of the first water-soluble polymer (specifically, a polyvinyl alcohol-based polymer) in the polishing composition can be set to, for example, 0.01 parts by weight or more relative to 100 parts by weight of abrasive grains (typically silica particles). From the perspective of reducing defects, it is appropriate to set it to 0.1 parts by weight or more, preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, and it can be 1.5 parts by weight or more, 2 parts by weight or more, 3 parts by weight or more, or 3.5 parts by weight or more. The content of the first water-soluble polymer relative to 100 parts by weight of abrasive grains can be, for example, 50 parts by weight or less, or 30 parts by weight or less. From the perspective of the dispersion stability of the polishing composition, in some embodiments, it is appropriate to set the content of the first water-soluble polymer relative to 100 parts by weight of abrasive grains to 15 parts by weight or less, preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and it can be less than 3 parts by weight, 2.5 parts by weight or less, or 2 parts by weight or less. By appropriately setting the usage-amount of the first water-soluble polymer (specifically, the polyvinyl alcohol-based polymer) within the above-mentioned range, high surface quality after polishing can be achieved.
[0109] <Second water-soluble polymer>
[0110] The polishing composition disclosed herein includes a second water-soluble polymer in addition to a first water-soluble polymer (specifically, a polyvinyl alcohol-based polymer). The second water-soluble polymer is typically a polymer having a chemical structure different from that of the first water-soluble polymer. As long as the product of the zeta potential ζ [mV] of the polishing composition and the etching rate ER [μm / h] of the polishing composition satisfies the above-mentioned specific conditions, there is no particular limitation on the second water-soluble polymer, and various substances can be used.
[0111] As the second water-soluble polymer, compounds containing hydroxyl, carboxyl, acyloxy, sulfonic, amide, imide, quaternary ammonium, heterocyclic, vinyl, etc. in the molecule can be cited. As the second water-soluble polymer, for example, cellulose derivatives, starch derivatives, polymers containing oxyalkylene units, polyvinyl alcohol polymers, polymers containing nitrogen atoms, polymers containing (meth) acrylic acid units, etc. can be used. As one form of polymers containing nitrogen atoms, N-vinyl polymers, N-(meth)acryloyl polymers, etc. can be used. The second water-soluble polymer can be a polymer derived from natural products or a synthetic polymer.
[0112] In some embodiments, a polymer derived from natural products is used as the second water-soluble polymer. Examples of the polymer derived from natural products include cellulose derivatives and starch derivatives.
[0113] In some embodiments, a cellulose derivative is used as the second water-soluble polymer. Here, the cellulose derivative is a polymer containing a β-glucose unit as a main repeating unit. Specific examples of cellulose derivatives include hydroxyethyl cellulose (HEC), hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, carboxymethyl cellulose, etc. Among them, HEC is preferred.
[0114] In other embodiments, a starch derivative is used as the second water-soluble polymer. The starch derivative is a polymer containing an α-glucose unit as a main repeating unit, and examples thereof include α-starch, pullulan, carboxymethyl starch, and cyclodextrin.
[0115] In some other preferred embodiments, a synthetic polymer is used as the second water-soluble polymer. The surface quality improvement effect disclosed herein can be preferably exerted in the embodiment using a synthetic polymer as the second water-soluble polymer.
[0116] In some ways, as the second water-soluble polymer, a polymer comprising an oxyalkylene unit is used. As a polymer comprising an oxyalkylene unit, block copolymers of polyethylene oxide (PEO), ethylene oxide (EO) and propylene oxide (PO) or butylene oxide (BO), random copolymers of EO and PO or BO, etc. can be exemplified. Wherein, preferably a block copolymer of EO and PO or a random copolymer of EO and PO. The block copolymer of EO and PO can be a diblock copolymer or a triblock copolymer comprising a PEO block and a polypropylene oxide (PPO) block, etc. The example of the above-mentioned triblock copolymer includes a PEO-PPO-PEO type triblock copolymer and a PPO-PEO-PPO type triblock copolymer. Usually, more preferably a PEO-PPO-PEO type triblock copolymer.
[0117] It should be noted that, in the present specification, unless otherwise specified, the term "copolymer" means various copolymers including random copolymers, alternating copolymers, block copolymers, graft copolymers, and the like.
[0118] In the block copolymer or random copolymer of EO and PO, from the viewpoint of solubility in water, washability, etc., the molar ratio of EO to PO constituting the copolymer (EO / PO) is preferably greater than 1, more preferably 2 or more, and further preferably 3 or more (e.g. 5 or more).
[0119] In some preferred embodiments, a polyvinyl alcohol polymer is used as the second water-soluble polymer. It should be noted that when the polishing composition comprises two or more polyvinyl alcohol polymers, the one with a smaller Mw is used as the first water-soluble polymer, and the one with a larger Mw is used as the second water-soluble polymer.
[0120] In some preferred embodiments, as the second water-soluble polymer, a modified PVA containing repeating units derived from N-vinyl monomers and N-(meth)acryloyl monomers as non-VA units can be used. In other embodiments when the second water-soluble polymer is a polyvinyl alcohol polymer, as the second water-soluble polymer, a polymer listed as a polyvinyl alcohol polymer that can be preferably used as the first water-soluble polymer can be used. The examples of preferred polymers are repeated and therefore omitted.
[0121] In other embodiments, as the second water-soluble polymer, an N-vinyl polymer can be used. Examples of N-vinyl polymers include polymers containing repeating units derived from monomers having nitrogen-containing heterocycles (e.g., lactam rings). Examples of such polymers include homopolymers and copolymers of N-vinyl lactam monomers (e.g., copolymers in which the copolymerization ratio of N-vinyl lactam monomers exceeds 50% by weight), homopolymers and copolymers of N-vinyl chain amides (e.g., copolymers in which the copolymerization ratio of N-vinyl chain amides exceeds 50% by weight), etc.
[0122] Specific examples of N-vinyl lactam monomers (i.e., compounds having a lactam structure and an N-vinyl group in one molecule) include N-vinyl pyrrolidone (VP), N-vinyl piperidone, N-vinyl morpholinone, N-vinyl caprolactam (VC), N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, etc. Specific examples of polymers containing N-vinyl lactam monomer units include polyvinyl pyrrolidone, polyvinyl caprolactam, random copolymers of VP and VC, random copolymers of one or both of VP and VC and other vinyl monomers (e.g., acrylic monomers, vinyl ester monomers, etc.), block copolymers containing polymer chains containing one or both of VP and VC, alternating copolymers, graft copolymers, etc.
[0123] Specific examples of the N-vinyl chain amide include N-vinylacetamide, N-vinylpropionic acid amide, and N-vinylbutyric acid amide.
[0124] In some other embodiments, as the second water-soluble polymer, an N-(meth)acryloyl type polymer can be used. Examples of N-(meth)acryloyl type polymers include homopolymers and copolymers of N-(meth)acryloyl type monomers (typically copolymers in which the copolymerization ratio of N-(meth)acryloyl type monomers exceeds 50 weight %). Examples of N-(meth)acryloyl type monomers include chain amides having N-(meth)acryloyl groups and cyclic amides having N-(meth)acryloyl groups. It should be noted that, in this specification, (meth)acryloyl type means including acryl type and methacryloyl type. In addition, in this specification, (meth)acryloyl means including acryl group and methacryloyl group.
[0125] Examples of chain amides having N-(meth)acryloyl groups include (meth)acrylamide; N-alkyl(meth)acrylamide such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N-n-butyl(meth)acrylamide; and N,N-dialkyl(meth)acrylamide such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. In addition, for example, N-hydroxyethylacrylamide (HEAA) can be cited. Examples of polymers containing chain amides having N-(meth)acryloyl groups as monomer units include homopolymers of N-isopropylacrylamide and copolymers of N-isopropylacrylamide (e.g., copolymers in which the copolymerization ratio of N-isopropylacrylamide exceeds 50% by weight). It should be noted that, in the present specification, (meth)acrylamide means including acrylamide and methacrylamide.
[0126] As examples of cyclic amides with N-(meth)acryloyl groups, N-acryloyl morpholine, N-acryloyl thiomorpholine, N-acryloyl piperidine, N-acryloyl pyrrolidine, N-methacryloyl morpholine, N-methacryloyl piperidine, N-methacryloyl pyrrolidine, etc. can be cited. As examples of polymers containing cyclic amides with N-(meth)acryloyl groups as monomer units, acryloyl morpholine polymers (PACMO) can be cited. As typical examples of acryloyl morpholine polymers, homopolymers of N-acryloyl morpholine (ACMO) and copolymers of ACMO (e.g., copolymers with a copolymerization ratio of ACMO exceeding 50% by weight) can be cited. In acryloyl morpholine polymers, the proportion of the number of moles of ACMO units in the number of moles of all repeating units is usually 50% or more, and it is appropriate to be 80% or more (e.g., 90% or more, typically 95% or more). The second water-soluble polymer may have all repeating units substantially composed of ACMO units.
[0127] In some embodiments, as the second water-soluble polymer, a carboxylic acid polymer is used. As examples of carboxylic acid polymers, polymers comprising maleic acid units, polymers comprising (meth) acrylic acid units, etc. can be listed. As examples of polymers comprising maleic acid units, styrene-maleic acid copolymers or their salts, styrene-maleic anhydride copolymers, styrene sulfonic acid-maleic acid copolymers or their salts, copolymers of styrene sulfonate and maleic acid, maleic acid-vinyl acetate copolymers, etc. can be listed. As examples of polymers comprising (meth) acrylic acid units, polyacrylic acid or their salts, styrene-acrylic acid copolymers or their salts, styrene sulfonic acid-acrylic acid copolymers or their salts, copolymers of styrene sulfonate and acrylic acid, acrylic acid-vinyl acetate copolymers, acrylic acid / sulfonic acid monomer copolymers, etc. can be listed. It should be noted that in this specification, (meth) acrylic acid refers to the meaning including acrylic acid and methacrylic acid.
[0128] When the second water-soluble polymer is a polyvinyl alcohol-based polymer, the Mw of the second water-soluble polymer can be, for example, 100×10 4 Below, 60×10 4 The following are appropriate. From the viewpoint of concentration efficiency, etc., the above Mw can be 30×10 4 Below, preferably 20×10 4 Below, for example, it can be 10×10 4 Below, can be 8×10 4 Below, can be 5×10 4 Below, it can also be 3×10 4 In addition, from the viewpoint of appropriately protecting the polished surface and maintaining or improving the surface quality, the Mw may be, for example, 0.2×10 4 Above, usually preferably 0.5×10 4 As the Mw of the polyvinyl alcohol polymer increases, the effect of protecting the polishing object and improving wettability tends to increase. From this point of view, in some embodiments, the Mw is 0.8×10 4 The above is appropriate, preferably 1.0×10 4 Above, it can also be 1.2×10 4 above.
[0129] When the second water-soluble polymer is a polymer containing a chain amide having an N-(meth)acryloyl group as a monomer unit, the Mw of the second water-soluble polymer can be, for example, 100×10 4 Below, 50×10 4 The following are appropriate. From the perspective of concentration efficiency, etc., the above Mw can be 30×10 4 Below, can be 10×10 4Below, can be 8×10 4 Below, can also be 6×10 4 From the viewpoint of improving the surface quality, the Mw may be, for example, 1×10 4 Above, it can be 2×10 4 Above, it can also be 3×10 4 More than (for example, 4×10 4 By using a second water-soluble polymer having a high Mw, a high surface quality can be easily obtained.
[0130] When the second water-soluble polymer is a polymer containing a cyclic amide having an N-(meth)acryloyl group as a monomer unit, the Mw of the second water-soluble polymer can be, for example, 100×10 4 Below, 70×10 4 The following are appropriate. From the perspective of concentration efficiency, etc., the above Mw can be 60×10 4 Below, can be 50×10 4 Below, can also be 40×10 4 From the viewpoint of improving the surface quality, the Mw may be, for example, 1.0×10 4 Above, can be 5×10 4 Above, it can also be 10×10 4 More than (for example, more than 10×10 4 ). In some embodiments, the Mw is 20×10 4 The above is appropriate, preferably 25×10 4 More preferably 30×10 4 More than (for example, more than 30×10 4 ). By using a second water-soluble polymer having a high Mw, a high surface quality can be easily obtained.
[0131] When the second water-soluble polymer is a polymer containing a (meth)acrylic acid unit, the Mw of the second water-soluble polymer can be, for example, 800×10 4 Below, 500×10 4 The following are appropriate. From the viewpoint of concentration efficiency, etc., the above Mw can be 300×10 4 Below, preferably 200×10 4 Below, for example, it can be 175×10 4 Below, can be 150×10 4 Below, can also be 140×10 4 In addition, from the viewpoint of appropriately protecting the polished surface and maintaining or improving the surface quality, the Mw may be, for example, 20×10 4 Above, can be 50×104 Above, it can also be 100×10 4 Above (for example, 130×10 4 By using a second water-soluble polymer having a high Mw, a high surface quality can be easily obtained.
[0132] When the second water-soluble polymer is a polymer containing an oxyalkylene unit, the Mw of the second water-soluble polymer can be set to 10×10 4 Below, can be 5×10 4 Below, can be 3×10 4 Below, it can also be 2×10 4 The above Mw can be set to 1×10 4 Above, it can be 1.2×10 4 Above, it can also be 1.5×10 4 above.
[0133] Although not particularly limited, in some embodiments, as the second water-soluble polymer, a polymer having a higher Mw than the first water-soluble polymer can be preferably used. By using two water-soluble polymers having the above relative Mw, high surface quality after polishing can be preferably achieved.
[0134] Although not particularly limited, in some embodiments, the content of the second water-soluble polymer in the grinding composition can be set to 0.01 weight parts or more relative to 100 weight parts of abrasive particles (typically silica particles). From the viewpoint of reducing haze, it is appropriate to set it to 0.1 weight parts or more, preferably 0.5 weight parts or more, more preferably 1 weight parts or more, and also 2 weight parts or more. In addition, the content of the second water-soluble polymer relative to 100 weight parts of abrasive particles can be, for example, 50 weight parts or less, or 30 weight parts or less. From the viewpoint of the dispersion stability of the grinding composition, in some embodiments, it is appropriate to set the content of the second water-soluble polymer relative to 100 weight parts of abrasive particles to 15 weight parts or less, preferably 10 weight parts or less, more preferably 5 weight parts or less, for example, 3.5 weight parts or less. By appropriately setting the usage amount of the second water-soluble polymer according to the above range, high surface quality can be obtained.
[0135] Although not particularly limited, in some embodiments, the ratio (B / (C1+C2)) of the content of the basic compound (B) in the polishing composition to the total content (C1+C2) of the water-soluble polymer can be, for example, 0.01 or more on a weight basis. From the viewpoint of polishing rate, etc., it is appropriate to set it to 0.1 or more, preferably 0.2 or more, more preferably 0.5 or more, and can also be 0.7 or more. In addition, the ratio (B / (C1+C2)) of the content of the basic compound (B) in the polishing composition to the total content (C1+C2) of the water-soluble polymer can be, for example, 15 or less, or 10 or less on a weight basis. In addition, from the viewpoint of appropriately protecting the polishing surface and maintaining or improving the surface quality, the above content ratio is appropriately 7 or less, preferably 5 or less, more preferably 2 or less, for example, 1 or less. By appropriately setting the ratio of the content of the basic compound (B) to the total content (C1+C2) of the water-soluble polymer according to the above range, a high surface quality can be obtained.
[0136] Although not particularly limited, in some embodiments, the total content of the water-soluble polymer contained in the grinding composition can be set to 0.01 parts by weight or more relative to 100 parts by weight of abrasive grains (typically silica particles). From the viewpoint of improving the surface quality, it is appropriate to set it to 0.1 parts by weight or more, preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, further preferably 2 parts by weight or more, particularly preferably 4 parts by weight or more, and it can also be 6 parts by weight or more. In addition, relative to 100 parts by weight of abrasive grains, the total content of the above-mentioned water-soluble polymers can be, for example, 50 parts by weight or less, or 30 parts by weight or less. From the viewpoint of the dispersion stability of the grinding composition, in some embodiments, relative to 100 parts by weight of abrasive grains, the total content of the above-mentioned water-soluble polymers is set to 15 parts by weight or less, preferably 12 parts by weight or less, and it can also be 10 parts by weight or less (for example, less than 10 parts by weight).
[0137] Although not particularly limited, in some embodiments, the ratio (W2 / W1) of the content W2 of the second water-soluble polymer relative to the content W1 of the first water-soluble polymer is, for example, 0.01 or more on a weight basis, 0.1 or more is appropriate, preferably 0.2 or more, 0.4 or more, 0.6 or more, or 0.8 or more. In addition, the upper limit of the above ratio (W2 / W1) is, for example, 10 or less on a weight basis, 5 or less is appropriate, preferably 3 or less, more preferably less than 2, or 1 or less (less than 1). By appropriately setting the above ratio (W2 / W1) within the above range, the effect of the technology disclosed herein can be preferably exerted.
[0138] The polishing composition disclosed herein may contain a water-soluble polymer other than the first water-soluble polymer and the second water-soluble polymer as an optional component (hereinafter also referred to as an optional water-soluble polymer) within a range that does not significantly impair the effects of the present invention.
[0139] In the embodiment where the polishing composition contains an optional water-soluble polymer, the content ratio of the optional water-soluble polymer in all water-soluble polymers contained in the polishing composition is not particularly limited. From the viewpoint of effectively exerting the effects of the first water-soluble polymer and the second water-soluble polymer, it is appropriate to set it to about 50% by weight or less (for example, less than 50% by weight), and it may be 30% by weight or less, less than 10% by weight, less than 3% by weight, or less than 1% by weight. The technology disclosed herein can be preferably implemented in an embodiment where the polishing composition does not substantially contain an optional water-soluble polymer.
[0140] <Surfactant>
[0141] In some embodiments, the polishing composition preferably includes at least one surfactant. By making the polishing composition contain a surfactant, the haze of the polished surface can be reduced. According to the technology disclosed herein, by including the combination of the above-mentioned water-soluble polymer and the composition of the surfactant, the quality of the polished surface can be further improved. As a surfactant, anionic, cationic, nonionic, and amphoteric surfactants can be used. Generally, anionic or nonionic surfactants can be preferably used. From the perspective of low foaming and ease of pH adjustment, nonionic surfactants are more preferred. For example, oxyalkylene polymers such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; polyoxyalkylene derivatives (such as polyoxyalkylene adducts) such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene fatty acid esters, polyoxyethylene glycerol ether fatty acid esters, and polyoxyethylene sorbitan fatty acid esters; copolymers of various oxyalkylenes (such as diblock copolymers, triblock copolymers, random copolymers, alternating copolymers) and other nonionic surfactants. The surfactant may be used alone or in combination of two or more.
[0142] Specific examples of the nonionic surfactant include block copolymers of ethylene oxide (EO) and propylene oxide (PO) (diblock copolymers, PEO (polyethylene oxide) -PPO (polypropylene oxide) -PEO type triblocks, PPO-PEO-PPO type triblock copolymers, etc.), random copolymers of EO and PO, polyoxyethylene glycol, polyoxyethylene propyl ether, polyoxyethylene butyl ether, polyoxyethylene pentyl ether, polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene isodecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene isostearyl ether, polyoxyethylene Ethyl oleyl ether, polyoxyethylene phenyl ether, polyoxyethylene octyl phenyl ether, polyoxyethylene nonyl phenyl ether, polyoxyethylene dodecyl phenyl ether, polyoxyethylene styrenated phenyl ether, polyoxyethylene laurylamine, polyoxyethylene stearylamine, polyoxyethylene oleylamine, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene distearate, polyoxyethylene monooleate, polyoxyethylene dioleate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, etc. Among them, as preferred surfactants, block copolymers of EO and PO (especially PEO-PPO-PEO type triblock copolymers), random copolymers of EO and PO, and polyoxyethylene alkyl ethers (e.g., polyoxyethylene decyl ether) can be listed. As polyoxyethylene alkyl ethers, polyoxyethylene alkyl ethers having an EO addition molar number of about 1 to 10 (e.g., about 3 to 8) are preferably used.
[0143] In some embodiments, it is preferable to use a nonionic surfactant. The use of a nonionic surfactant tends to further improve the haze reduction performance.
[0144] The molecular weight of the surfactant is, for example, less than 1×10 4, from the viewpoints of filterability and cleaning properties, it is preferably 9500 or less, for example, it can be less than 9000. In addition, from the viewpoints of surface activity, etc., it is appropriate that the molecular weight of the surfactant is usually 200 or more, and from the viewpoint of haze reduction effect, etc., it is preferably 250 or more (for example, 300 or more). The more preferred range of the molecular weight of the surfactant may also vary depending on the type of the surfactant. For example, when polyoxyethylene alkyl ether is used as a surfactant, its molecular weight is, for example, preferably less than 2000, more preferably less than 1900 (for example, less than 1800), further preferably less than 1500, and can also be less than 1000 (for example, less than 500). In addition, for example, when a block copolymer of EO and PO is used as a surfactant, its weight average molecular weight can be, for example, more than 500, more than 1000, more than 1500, more than 2000, or more than 2500. The upper limit of the above-mentioned weight average molecular weight is, for example, less than 1×10 4 , preferably less than 9500, for example, less than 9000, less than 7000, or less than 5000.
[0145] As the molecular weight of the surfactant, the molecular weight calculated by the chemical formula can be used, or the value of the weight average molecular weight obtained by GPC (water system, polyethylene glycol conversion) can be used. For example, in the case of polyoxyethylene alkyl ether, it is preferred to use the molecular weight calculated by the chemical formula, and in the case of the block copolymer of EO and PO, it is preferred to use the weight average molecular weight obtained by the above-mentioned GPC.
[0146] Although not particularly limited, in the case where the polishing composition includes a surfactant, from the viewpoint of cleaning properties, it is usually appropriate to set the content of the surfactant to 20 parts by weight or less, preferably 10 parts by weight or less, and more preferably 6 parts by weight or less (e.g., 3 parts by weight or less) relative to 100 parts by weight of abrasive grains (typically silica grains). From the viewpoint of better exerting the effect of the use of the surfactant, it is appropriate to set the content of the surfactant to 0.001 parts by weight or more, preferably 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, and may be 0.5 parts by weight or more relative to 100 parts by weight of abrasive grains.
[0147] <Water>
[0148] As the water contained in the polishing composition disclosed herein, ion exchange water (deionized water), pure water, ultrapure water, distilled water, etc. can be preferably used. In order to avoid the effects of other components contained in the polishing composition being inhibited as much as possible, the water used, for example, preferably has a total content of transition metal ions below 100 ppb. For example, the purity of water can be improved by removing impurity ions using ion exchange resins, removing foreign matter using filters, and distilling. It should be noted that the polishing composition disclosed herein can also further contain an organic solvent (lower alcohol, lower ketone, etc.) that can be uniformly mixed with water as needed. Preferably, 90% by volume or more of the solvent contained in the polishing composition is water, and more preferably 95% by volume or more (for example, 99 to 100% by volume) is water.
[0149] <Other ingredients>
[0150] The polishing composition disclosed herein may further contain known additives such as organic acids, organic acid salts, inorganic acids, inorganic acid salts, chelating agents, preservatives, and mildew inhibitors that can be used in polishing compositions (e.g., polishing compositions used in the fine polishing process of silicon wafers) as needed, within the range that does not significantly hinder the effects of the present invention.
[0151] Organic acids and salts thereof, and inorganic acids and salts thereof can be used alone or in combination of two or more. Examples of organic acids include fatty acids such as formic acid, acetic acid, propionic acid, aromatic carboxylic acids such as benzoic acid and phthalic acid, itaconic acid, citric acid, oxalic acid, tartaric acid, malic acid, maleic acid, fumaric acid, succinic acid, glycolic acid, malonic acid, gluconic acid, alanine, glycine, lactic acid, hydroxyethylidene diphosphoric acid (HEDP), organic sulfonic acids such as methanesulfonic acid, organic phosphonic acids such as nitrilotris(methylenephosphoric acid) (NTMP), and phosphonobutanetricarboxylic acid (PBTC). Examples of organic acid salts include alkali metal salts (sodium salts, potassium salts, etc.) and ammonium salts of organic acids. Examples of inorganic acids include hydrochloric acid, phosphoric acid, sulfuric acid, phosphonic acid, nitric acid, phosphinic acid, boric acid, and carbonic acid. Examples of inorganic acid salts include alkali metal salts (sodium salts, potassium salts, etc.) and ammonium salts of inorganic acids.
[0152] The above-mentioned chelating agent can be used alone or in combination of two or more. Examples of the above-mentioned chelating agent include aminocarboxylic acid chelating agents and organic phosphonic acid chelating agents. Suitable examples of the chelating agent include ethylenediaminetetrakis (methylenephosphonic acid), diethylenetriaminepenta (methylenephosphonic acid) and diethylenetriaminepentaacetic acid. Examples of the above-mentioned preservatives and mildewproofing agents include isothiazolin compounds, parabens, phenoxyethanol, etc.
[0153] The grinding composition disclosed herein is preferably substantially free of oxidant. This is because, when the grinding composition includes an oxidant, the grinding composition is supplied to a substrate (such as a silicon wafer), so that the surface of the substrate is oxidized to produce an oxide film, and the grinding rate may be reduced. As a specific example of the oxidant mentioned here, hydrogen peroxide (H2O2), sodium persulfate, ammonium persulfate, sodium dichloroisocyanurate, etc. can be listed. It should be noted that the grinding composition substantially does not contain an oxidant, which means that at least it does not intentionally contain an oxidant. Therefore, the grinding composition that inevitably contains a trace amount of oxidant (for example, the molar concentration of the oxidant in the grinding composition is 0.001 mol / L or less, preferably 0.0005 mol / L or less, more preferably 0.0001 mol / L or less, further preferably 0.00005 mol / L or less, particularly preferably 0.00001 mol / L or less) due to raw materials, preparation methods, etc. can be included in the concept of the grinding composition substantially free of oxidant mentioned here.
[0154] <ph>
[0155] The pH of the polishing composition disclosed herein is not particularly limited, and an appropriate pH can be adopted according to the substrate, etc. In some embodiments, the pH of the polishing composition is appropriately 8.0 or more, preferably 8.5 or more, and more preferably 9.0 or more. If the pH of the polishing composition becomes high, there is a tendency for the polishing rate to increase. On the other hand, from the viewpoint of preventing the dissolution of the silica particles and suppressing the reduction of the mechanical polishing effect, the pH of the polishing composition is usually appropriately 12.0 or less, preferably 11.0 or less, more preferably 10.8 or less, and further preferably 10.5 or less.
[0156] It should be noted that in the technology disclosed herein, the pH of the polishing composition can be determined as follows: using a pH meter (e.g., a glass electrode hydrogen ion concentration indicator (model F-72) manufactured by Horiba, Ltd.), after performing a three-point calibration using a standard buffer solution (phthalate pH buffer solution pH: 4.01 (25°C), neutral phosphate pH buffer solution pH: 6.86 (25°C), carbonate pH buffer solution pH: 10.01 (25°C)), the glass electrode is inserted into the composition to be measured, and the value after stabilization for more than 2 minutes is measured.
[0157] <Polishing fluid>
[0158] The grinding composition disclosed herein is typically supplied to the surface of the substrate in the form of a grinding liquid comprising the grinding composition, and is used for the grinding of the substrate. The above-mentioned grinding liquid can be, for example, a grinding liquid prepared by diluting any grinding composition disclosed herein (typically diluted with water). Alternatively, the grinding composition can also be used directly as a grinding liquid. As other examples of the grinding liquid comprising the grinding composition disclosed herein, a grinding liquid formed by adjusting the pH of the composition can be listed.
[0159] The content of abrasive grains (typically silica particles) in the polishing liquid is not particularly limited, for example, 0.005% by weight or more, preferably 0.01% by weight or more, more preferably 0.03% by weight or more, and further preferably 0.06% by weight or more. With the increase of the content of abrasive grains, a higher polishing rate can be achieved. It is appropriate that the above content is 10% by weight or less, preferably 7% by weight or less, more preferably 5% by weight or less, and further preferably 2% by weight or less, for example, 1% by weight or less, 0.5% by weight or less, or 0.4% by weight or less. Thus, it is easy to maintain the surface quality.
[0160] The content of the alkaline compound in the polishing liquid is not particularly limited. From the viewpoints of improving the polishing rate, it is usually appropriate to set the above content to more than 0.0005 weight %, preferably to more than 0.001 weight %, and further preferably to more than 0.003 weight %. In addition, from the viewpoints of improving the surface quality (for example, reducing the haze), it is appropriate to set the above content to less than 0.1 weight %, preferably to less than 0.05 weight %, and more preferably to less than 0.03 weight % (for example, less than 0.025 weight %, further less than 0.01 weight %).
[0161] Although not particularly limited, in some ways, from the perspective of improving surface quality, the content W1 of the first water-soluble polymer (specifically, a polyvinyl alcohol-based polymer) in the polishing liquid can be, for example, 0.0001% by weight or more, and it is usually appropriate to set it to 0.0005% by weight or more, preferably 0.001% by weight or more, for example, it can be 0.002% by weight or more, or it can be 0.003% by weight or more. The upper limit of the content W1 of the above-mentioned first water-soluble polymer is not particularly limited, for example, it can be set to 0.05% by weight or less. From the perspective of stability, polishing rate, cleaning properties, etc. in the concentrated liquid stage, in some ways, the content W1 of the first water-soluble polymer is preferably 0.03% by weight or less, more preferably 0.015% by weight or less, and further preferably 0.01% by weight or less. The polishing liquid disclosed herein can also be implemented in a manner such as the content W1 of the first water-soluble polymer is 0.008% by weight or less, 0.006% by weight or less, or 0.004% by weight or less.
[0162] Although not particularly limited, in some ways, from the viewpoint of improving surface quality, the content W2 of the second water-soluble polymer in the polishing liquid can be, for example, 0.0001% by weight or more, and it is usually appropriate to set it to 0.0005% by weight or more, preferably 0.001% by weight or more, more preferably 0.002% by weight or more, 0.003% by weight or more, or 0.005% by weight or more. The upper limit of the content W2 of the second water-soluble polymer is not particularly limited, for example, it can be set to 0.1% by weight or less. From the viewpoint of stability, polishing rate, cleaning properties, etc. in the concentrated liquid stage, in some ways, the content W2 of the second water-soluble polymer is preferably 0.05% by weight or less, more preferably 0.02% by weight or less, and further preferably 0.01% by weight or less.
[0163] The total content of the water-soluble polymer in the polishing liquid is not particularly limited, and in some ways, for example, can be set to more than 0.0001 weight %. From the viewpoints of reducing haze, the above-mentioned total content is preferably more than 0.0005 weight %, more preferably more than 0.001 weight %, and further preferably more than 0.002 weight %, for example, can be more than 0.005 weight %. In addition, the upper limit of the above-mentioned total content is, for example, less than 0.5 weight %, and from the viewpoints of polishing rate, it is preferably set to less than 0.2 weight %, more preferably set to less than 0.1 weight %, and further preferably set to less than 0.05 weight % (for example, less than 0.02 weight %, further less than 0.015 weight %).
[0164] When a surfactant is included, the content of the surfactant in the polishing liquid (when two or more surfactants are included, the total content thereof) is not particularly limited as long as it does not significantly hinder the effect of the present invention. Usually, from the viewpoints of cleaning properties, the content of the above-mentioned surfactant can be, for example, set to more than 0.00001% by weight. From the viewpoints of reducing haze, the preferred content is more than 0.0001% by weight, more preferably more than 0.0003% by weight, and more preferably more than 0.0005% by weight. In addition, from the viewpoints of polishing rate, it is preferred that the above-mentioned content is set to less than 0.1% by weight, more preferably less than 0.01% by weight, and more preferably less than 0.005% by weight (for example, less than 0.002% by weight).
[0165] <Concentrate>
[0166] The grinding composition disclosed herein may be in a concentrated form (i.e., in the form of a concentrated solution of the grinding liquid) before being supplied to the substrate. This concentrated grinding composition is advantageous from the viewpoints of convenience, cost reduction, etc. during manufacture, circulation, and storage. The concentration ratio is not particularly limited, and for example, it may be set to be about 2 to 100 times in volume conversion, and generally about 5 to 50 times (e.g., about 10 to 40 times) is appropriate. Such a concentrated solution can be used in a manner of preparing a grinding liquid (working slurry) by diluting it at a desired time and supplying the grinding liquid to the substrate. The above-mentioned dilution can be performed, for example, by adding water to the above-mentioned concentrated solution and mixing it.
[0167] When the polishing composition (i.e., concentrated solution) is diluted and used for polishing, the content of the abrasive in the concentrated solution can be set to, for example, 25% by weight or less. From the viewpoints of dispersion stability and filterability of the polishing composition, the above content is usually preferably 20% by weight or less, more preferably 15% by weight or less. In some preferred embodiments, the content of the abrasive can be set to 10% by weight or less, or 5% by weight or less. In addition, from the viewpoints of convenience during manufacture, circulation, storage, etc., cost reduction, etc., the content of the abrasive in the concentrated solution can be set to, for example, 0.1% by weight or more, preferably 0.5% by weight or more, more preferably 0.7% by weight or more, and further preferably 1% by weight or more.
[0168] In some embodiments, the content of the alkaline compound in the above-mentioned concentrated solution can be set to, for example, less than 0.25% by weight. From the viewpoint of storage stability, the above-mentioned content is usually preferably 0.15% by weight or less, and more preferably 0.1% by weight or less. In addition, from the viewpoints of convenience during manufacture, circulation, storage, etc., cost reduction, etc., the content of the alkaline compound in the concentrated solution can be set to, for example, 0.005% by weight or more, preferably 0.01% by weight or more, more preferably 0.02% by weight or more, and further preferably 0.05% by weight or more.
[0169] In some embodiments, the total content of the water-soluble polymer in the above-mentioned concentrate can be set to, for example, 3% by weight or less. From the viewpoints of filterability and cleanability of the polishing composition, the above-mentioned content is usually preferably 1% by weight or less, and more preferably 0.5% by weight or less. In addition, from the viewpoints of convenience during manufacture, circulation, storage, etc., cost reduction, etc., it is appropriate that the above-mentioned content is usually 0.001% by weight or more, preferably 0.005% by weight or more, and more preferably 0.01% by weight or more.
[0170] In the embodiment in which the polishing composition contains a surfactant, the content of the surfactant in the concentrated solution can be, for example, 0.25 wt% or less, preferably 0.15 wt% or less, more preferably 0.1 wt% or less, 0.05 wt% or less, or 0.025 wt% or less. In addition, the content of the surfactant in the concentrated solution can be, for example, 0.0001 wt% or more, preferably 0.001 wt% or more, more preferably 0.005 wt% or more, and even more preferably 0.01 wt% or more.
[0171] <Preparation of Polishing Composition>
[0172] The polishing composition used in the technology disclosed herein may be a single-component type or a multi-component type including a two-component type. For example, it may be composed in the following manner: a part A containing at least abrasive grains among the constituent components of the polishing composition is mixed with a part B containing at least a part of the remaining components, and these are mixed and diluted at an appropriate time as needed to prepare a polishing liquid.
[0173] The preparation method of the grinding composition is not particularly limited. For example, known mixing devices such as a blade stirrer, an ultrasonic disperser, and a homogenizer can be used to mix the components constituting the grinding composition. The embodiment of mixing these components is not particularly limited, for example, all the components can be mixed at once, or they can be mixed in a sequence appropriately set.
[0174] <Purpose>
[0175] The polishing composition disclosed herein can be applied to the polishing of substrates having various materials and shapes. The material of the substrate can be, for example, metals or semi-metals such as silicon materials, aluminum, nickel, tungsten, copper, tantalum, titanium, stainless steel, or their alloys; glassy substances such as quartz glass, aluminosilicate glass, and glassy carbon; ceramic materials such as aluminum oxide, silicon dioxide, sapphire, silicon nitride, tantalum nitride, and titanium carbide; compound semiconductor substrate materials such as silicon carbide, gallium nitride, and gallium arsenide; resin materials such as polyimide resins, etc. It can also be a substrate composed of multiple materials among them. The shape of the substrate is not particularly limited. The polishing composition disclosed herein can be applied to the polishing of substrates having a flat surface such as a plate or a polyhedron, or the polishing of the end of a substrate (such as the polishing of a wafer edge).
[0176] The polishing composition disclosed herein can be particularly preferably used for polishing a surface formed by a silicon material (typically polishing a silicon wafer). As specific examples of silicon materials, single crystal silicon, amorphous silicon and polycrystalline silicon etc. can be listed. The polishing composition disclosed herein can be particularly preferably used for polishing a surface formed by a single crystal silicon (e.g. polishing a silicon wafer).
[0177] The grinding composition disclosed herein can be preferably applied to the polishing process of a substrate (e.g., silicon wafer). For the substrate, before the polishing process performed using the grinding composition disclosed herein, general processing such as grinding and etching that can be applied to the substrate in a process further upstream of the polishing process can be implemented.
[0178] The grinding composition disclosed herein is effective for the finishing process of a substrate (e.g., a silicon wafer) or the polishing process immediately before it, and is particularly preferably used in the fine polishing process. Here, the fine polishing process refers to the last polishing process in the manufacturing process of the target object (i.e., a process in which no further polishing is performed after the process). In addition, the grinding composition disclosed herein can also be used for a polishing process upstream of the fine polishing (referring to a pre-polishing process between a rough grinding process and a final grinding process. Typically, it includes at least one polishing process, and further may include two, three, etc. polishing processes), for example, a polishing process performed immediately before the fine polishing.
[0179] The polishing composition disclosed herein is effective, for example, in the polishing (typically fine polishing or the polishing immediately before) of a silicon wafer adjusted to a surface state of a surface roughness of 0.01 nm to 100 nm by an upstream process. It is particularly preferably applied to fine polishing. The surface roughness Ra of the substrate can be measured, for example, using a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt MeasurementSystem Inc.
[0180] <Grinding>
[0181] The polishing composition disclosed herein can be used for polishing a substrate in a manner including the following operations, for example. A preferred embodiment of a method for polishing a silicon wafer as a substrate using the polishing composition disclosed herein will be described below.
[0182] That is, a polishing liquid comprising any of the polishing compositions disclosed herein is prepared. When preparing the above-mentioned polishing liquid, the step of preparing the polishing liquid by performing operations such as concentration adjustment (e.g., dilution) and pH adjustment on the polishing composition may be included. Alternatively, the polishing composition may be directly used as the polishing liquid.
[0183] Next, the polishing liquid is supplied to the substrate and polished by conventional methods. For example, in the case of fine polishing of a silicon wafer, typically, the silicon wafer that has undergone a grinding process is placed in a general polishing device, and the polishing liquid is supplied to the polishing target surface of the above-mentioned silicon wafer through the polishing pad of the polishing device. Typically, while the above-mentioned polishing liquid is continuously supplied, the polishing pad is pressed against the polishing target surface of the silicon wafer, and the two are moved relative to each other (for example, rotationally moved). After this polishing process, the polishing of the substrate is completed.
[0184] The grinding pad used in the above-mentioned grinding process is not particularly limited. For example, a foamed polyurethane type, a nonwoven type, a suede type or other grinding pads can be used. Each grinding pad can contain abrasive particles or can contain no abrasive particles. Usually, a grinding pad that does not contain abrasive particles is preferably used.
[0185] The substrate polished using the polishing composition disclosed herein is typically cleaned. Cleaning can be performed using an appropriate cleaning solution. The cleaning solution used is not particularly limited. For example, in the field of semiconductors, general SC-1 cleaning solution (a mixture of ammonium hydroxide (NH4OH), hydrogen peroxide (H2O2) and water (H2O)), SC-2 cleaning solution (a mixture of HCl, H2O2 and H2O), etc. can be used. The temperature of the cleaning solution can be set, for example, to a range of above room temperature (typically about 15°C to 25°C) to about 90°C. From the viewpoint of improving the cleaning effect, a cleaning solution of about 50°C to 85°C can be preferably used.
[0186] As described above, the technology disclosed herein may include: providing a method for manufacturing a polished product (eg, a method for manufacturing a silicon wafer) including a polishing step (preferably fine polishing) using any of the above-mentioned polishing methods, and a polished product (eg, a silicon wafer) manufactured by the method.
[0187] Example
[0188] The following describes some embodiments related to the present invention, but it is not intended to limit the present invention to the contents shown in the embodiments. It should be noted that in the following description, "parts" and "%" are weight references unless otherwise specified.
[0189] <Preparation of Polishing Composition>
[0190] (Example 1)
[0191] Abrasive grains, alkaline compounds, water-soluble polymers, surfactants, and deionized water were mixed to prepare a concentrated solution of the polishing composition of each example. Colloidal silica with an average primary particle size of 25 nm was used as the abrasive grains. Ammonia was used as the alkaline compound. A water-soluble polymer with a Mw of about 1.3×10 4 Acetalized polyvinyl alcohol (ac-PVA; the first water-soluble polymer, acetalization degree 24 mol%) and a vinyl alcohol unit and an N-vinyl pyrrolidone unit in a molar ratio of 90:10, with a Mw of about 1.4×10 4 A random copolymer of PVA-r-PVP (the second water-soluble polymer) was prepared. As a surfactant, polyoxyethylene decyl ether (C10EO5) having an ethylene oxide addition mole number of 5 was used. The obtained concentrated solution of the polishing composition was diluted with deionized water to a volume ratio of 40 times, thereby obtaining polishing compositions of each example having an abrasive concentration of 0.08%, an alkaline compound concentration of 0.005%, an ac-PVA concentration of 0.003%, a PVA-r-PVP concentration of 0.001%, and a C10EO5 concentration of 0.0006%.
[0192] (Example 2)
[0193] As the second water-soluble polymer, a polymer having a Mw of 4.9×10 4 Poly(N-hydroxyethylacrylamide) (PHEAA) was added. The concentration of PHEAA was set to 0.002%. The polishing composition of this example was prepared in the same manner as in Example 1.
[0194] (Example 3)
[0195] As the first water-soluble polymer, an alkyl-modified PVA (hydrophobic-modified PVA) with a Mw of about 6000 was used, and as the second water-soluble polymer, an alkyl-modified PVA with a Mw of about 35×10 4 Polyacryloylmorpholine (PACMO) was added. In addition, the concentration of PACMO was set to 0.004%. The polishing composition of this example was prepared in the same manner as in Example 1. The alkyl-modified PVA used in this example is a random copolymer having vinyl alcohol units and n-propyl vinyl ether units in a molar ratio of 85:15.
[0196] (Example 4)
[0197] As the first water-soluble polymer, a polymer having a Mw of about 7.0×10 4 , fully saponified (saponification degree 98% or more) polyvinyl alcohol (PVA), as the second water-soluble polymer, with a Mw of about 136×10 4 In addition, the concentration of PVA was set to 0.003%, and the concentration of PAA was set to 0.005%. The other operations were carried out in the same manner as in Example 3 to prepare the polishing composition of this example.
[0198] (Example 5)
[0199] The concentration of the basic compound was set to 0.010%. The polishing composition of this example was prepared in the same manner as in Example 4.
[0200] (Example 6)
[0201] The concentration of the basic compound was set to 0.015%. The polishing composition of this example was prepared in the same manner as in Example 4.
[0202] (Comparative Example 1)
[0203] As the second water-soluble polymer, poly(vinyl methyl ether) (PVME) was used. The concentration of PVME was set to 0.003%. The polishing composition of this example was prepared in the same manner as in Example 1.
[0204] (Comparative Example 2)
[0205] As the first water-soluble polymer, butylene glycol-vinyl alcohol copolymer (BVOH) having a 1,2-diol structure in the side chain and an Mw of 20,000 was used. As the second water-soluble polymer, polyacrylmorpholine (PACMO) of about 35×10 4 was used. In addition, the concentration of BVOH was set to 0.003% and the concentration of PACMO was set to 0.004%. Otherwise, the same operations as in Example 1 were performed to prepare the polishing composition of this example. The saponification degree of the butylene glycol-vinyl alcohol copolymer was 95% or more.
[0206] (Comparative Example 3)
[0207] As the first water-soluble polymer, polyvinyl alcohol (PVA) having an Mw of about 7.0×10 4 and completely saponified (saponification degree of 98% or more) was used. As the second water-soluble polymer, hydroxyethyl cellulose (HEC) having an Mw of about 28×10 4 was used. In addition, the concentration of PVA was set to 0.003% and the concentration of HEC was set to 0.009%. In addition, the concentration of C10EO5 was set to 0.0005%. Otherwise, the same operations as in Example 1 were performed to prepare the polishing composition of this example.
[0208] (Measurement of Zeta potential)
[0209] For each polishing composition, the Zeta potential ζ [mV] was measured using a Zeta potential measuring device under the following conditions. As the measuring device, the model name "Zetasizer nano ZSP" manufactured by Malvern was used. The measurement results are shown in the corresponding columns of Table 1.
[0210] (Zeta potential measurement conditions)
[0211] Dispersion medium: water
[0212] Measurement temperature: 25°C
[0213] Model: Smoluchowski
[0214] For each polishing composition, the etching rate ER [μm / h] was determined based on the etching rate measurement. The obtained results are shown in Table 1.
[0215] For the polishing composition of each example, the product (ζ×ER) [nmV / h] of the Zeta potential ζ [mV] and the etching rate ER [μm / h] was calculated. The obtained values are shown in the corresponding columns of Table 1.
[0216] (Polishing of silicon wafers)
[0217] As a substrate, a commercially available single crystal silicon wafer (conductivity type: P type, crystal orientation: <100> , COP-free (Crystal Originated Particle) silicon wafers were pre-polished under the following polishing conditions 1. The pre-polishing was performed using a polishing liquid containing 0.6% abrasive (colloidal silica with an average primary particle size of 35 nm) and 0.08% tetramethylammonium hydroxide (TMAH) in deionized water.
[0218] [Grinding Condition 1]
[0219] Grinding device: Single-wafer grinding device model "PNX-332B" manufactured by Okamoto Machine Tool Co., Ltd.
[0220] Grinding load: 20kPa
[0221] Plate speed: 20rpm
[0222] Grinding head (carrier) speed: 20rpm
[0223] Polishing pad: FUJIBO Ehime Co., Ltd., product name "FP55"
[0224] Grinding liquid supply rate: 1.0L / min
[0225] Grinding fluid temperature: 20°C
[0226] Plate cooling water temperature: 20℃
[0227] Grinding time: 2min
[0228] The pre-polished silicon wafer was polished under the following polishing conditions 2 using the polishing composition of each example prepared above as a polishing liquid.
[0229] [Grinding Condition 2]
[0230] Grinding device: Single-wafer grinding device model "PNX-332B" manufactured by Okamoto Machine Tool Co., Ltd.
[0231] Grinding load: 20kPa
[0232] Plate speed: 52rpm
[0233] Grinding head (carrier) speed: 50rpm
[0234] Polishing pad: FUJIBO Ehime Co., Ltd., product name "POLYPAS275NX"
[0235] Grinding liquid supply rate: 1.5L / min
[0236] Temperature of the polishing liquid: 20°C
[0237] Temperature of the flat plate cooling water: 20°C
[0238] Polishing time: 4 min
[0239] Remove the polished silicon wafer from the polishing apparatus and clean it (SC-1 cleaning) using a cleaning solution of NH4OH (29%): H2O2 (31%): deionized water (DIW) = 2:5.3:48 (volume ratio). More specifically, prepare a first cleaning tank equipped with an ultrasonic oscillator, store the above cleaning solution in the first cleaning tank, maintain it at 70°C, and immerse the polished silicon wafer in the cleaning tank for 6 minutes. Then, immerse it in a second cleaning tank filled with deionized water (DIW) at 25°C for 15 minutes, then immerse it in the first cleaning tank for 6 minutes and in the second cleaning tank for 16 minutes again, and then dry the silicon wafer.
[0240] <Measurement of LPD-N and haze lines>
[0241] Use a wafer inspection device manufactured by KLA-Tencor Corporation, trade name "Surfscan SP5", to measure the number of LPD-N and haze lines present on the surface of the cleaned silicon wafer in the DC mode of the device. The measured number of LPD-N is shown in Table 1. In addition, convert the measured haze lines to relative values when the haze lines of Comparative Example 1 are set to 10,000, and show this value in Table 1. It should be noted that LPD-N refers to Light Point Defect Non-cleanable. In addition, the haze line refers to the total area of minute scratches within the measurement area measured by the above inspection device.
[0242] Show the outlines and evaluation results of each example in Table 1. It should be noted that in the table, "-" indicates that it could not be measured or was not measured.
[0243] [Table 1]
[0244]
[0245] As shown in Table 1, according to the polishing compositions of Examples 1 to 6 containing a polyvinyl alcohol-based polymer as the first water-soluble polymer and a second water-soluble polymer having a chemical structure different from that of the first water-soluble polymer in a polishing composition containing silica particles, an alkaline compound, and water, and the product (ζ × ER) of the Zeta potential ζ [mV] and the etching rate ER [μm / h] is -900 nmV / h or more and -90 nmV / h or less, compared with the polishing compositions of Comparative Examples 1 to 3 where the above (ζ × ER) is greater than -90 nmV / h, both the number of LPD-N and the haze lines are significantly reduced, achieving high surface quality.
[0246] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.< / ph>
Claims
1. A polishing composition comprising: silica particles (A) as abrasive particles, a basic compound (B), a first water-soluble polymer (C1), a second water-soluble polymer (C2) and water (D), The first water-soluble polymer (C1) is a polyvinyl alcohol-based polymer, The product (ER×ζ) of the etching rate ER [μm / h] of the polishing composition and the zeta potential ζ [mV] of the polishing composition based on the following etching rate measurement is -900 nmV / h or more and -90 nmV / h or less, The etching rate is determined as: (1) preparing a polishing composition as a chemical solution LE for etching rate measurement; (2) A rectangular silicon single crystal substrate with a length of 6 cm, a width of 3 cm, and a thickness of 775 μm was prepared and its mass W0 was measured. The silicon single crystal substrate was immersed in a cleaning solution of NH4OH (29%):H2O2 (31%):deionized water (DIW) = 2:5.3:48 (volume ratio) at 25°C for 1 minute, and then immersed in a hydrogen fluoride (HF) aqueous solution (5%) at 25°C for 30 seconds; (3) immersing the silicon single crystal substrate in the chemical solution LE at 25° C. for 48 hours; (4) taking out the silicon single crystal substrate from the chemical solution LE, and cleaning it at 25° C. for 10 seconds with a cleaning solution of NH 4 OH (29%): H 2 O 2 (31%): deionized water (DIW) = 1:1:8 (volume ratio); (5) measuring the mass W1 of the cleaned silicon single crystal substrate; and (6) The etching rate [μm / h] is calculated based on the difference between W0 and W1 and the specific gravity of the silicon single crystal substrate.
2. The polishing composition according to claim 1, wherein The first water-soluble polymer (C1) is one or more selected from the group consisting of unmodified polyvinyl alcohol having a saponification degree of 70% or more, acetalized polyvinyl alcohol polymers, and polyvinyl alcohol polymers containing repeating units derived from alkyl vinyl ethers.
3. The polishing composition according to claim 1 or 2, wherein The content of the first water-soluble polymer (C1) is 0.5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the abrasive.
4. The polishing composition according to any one of claims 1 to 3, wherein The second water-soluble polymer (C2) is one or more selected from the group consisting of a polyvinyl alcohol polymer having a chemical structure different from that of the first water-soluble polymer (C1), a polymer containing a nitrogen atom, and a polymer containing a (meth)acrylic acid unit.
5. The polishing composition according to claim 4, wherein The nitrogen atom-containing polymer is a polymer containing, as a monomer unit, a chain amide having an N-(meth)acryloyl group.
6. The polishing composition according to any one of claims 1 to 5, wherein The content of the second water-soluble polymer (C2) is 0.5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the abrasive. 7 . The polishing composition according to claim 1 , further comprising a surfactant (E).
8. The polishing composition according to claim 7, wherein The surfactant (E) is a nonionic surfactant. 9 . The polishing composition according to claim 1 , which is used for polishing a surface formed of a silicon material.
10. The concentrated polishing composition according to any one of claims 1 to 9.
Citation Information
Patent Citations
Reducing of metal oxide containing material
JP1987032243B2
Continuous annealing furnace of meal strip
JP1988048927B2
Novel peptides
JP2022058671A